Innocents on the Ice : A Memoir of Antarctic Exploration, 1957 - Behrendt, John C., 1932- (Book collections on Project MUSE., 1998)
Drawing on his 40 years of Antarctic research experience, Behrendt explains the changes in scientific activities and environmental awareness in Antarctica today.